Payment changes and default risk: The impact of refinancing on expected credit losses - Joseph Tracy; Joshua Wright (Federal Reserve Bank of New York, 2012)
This paper analyzes the relationship between changes in borrowers' monthly mortgage payments and future credit performance. This relationship is important for the design of an internal refinance program such as the Home Affordable Refinance Program (HARP). We use a competing risk model to estimate the sensitivity of default risk to downward adjustments of borrowers' monthly mortgage payments for a large sample of prime adjustable-rate mortgages. Applying a 26 percent average monthly payment reduction that we estimate would result from refinancing under HARP, we find that the cumulative five-year default rate on prime conforming adjustable-rate mortgages with loan-to-value ratios above 80 percent declines by 3.8 percentage points. If we assume an average loss given default of 35.2 percent, this lower default risk implies reduced credit losses of 134 basis points per dollar of balance for mortgages that refinance under HARP.
Keywords: G21; G18; R51; 330; refinancing; default